2022
DOI: 10.1021/acsestwater.2c00182
|View full text |Cite
|
Sign up to set email alerts
|

Copper Pipe, Lack of Corrosion Control, and Very Low pH May Have Influenced the Trajectory of the Flint Legionnaires’ Disease Outbreak

Abstract: Uncertainties remain regarding factors influencing the Legionnaires' disease (LD) outbreaks in Flint, MI, after the city switched source waters and interrupted corrosion control. Notably, there was lower incidence of LD associated with residential versus hospital exposure in summer 2015 versus 2014. To test possible causes for this phenomenon, we designed a bench-scale study with an influent pH of 7.3, which demonstrated prolific growth of Legionella pneumophila in the presence of cross-linked polyethylene (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In paired samples where pH was measured ( n = 27), pH was significantly different between first-draw and flushed samples ( p < 0.05). pH may influence the occurrence of L. pneumophila in distribution systems and building water, 108 though one laboratory study reported that L. pneumophila can grow in water with pH values ranging from 5.5 to 9.2. 103 A 2021 cooling tower study suggested that high pH (9.6) may be a technique for L. pneumophila control, though the authors noted this may be related to a reduction in protozoan hosts at high pH.…”
Section: Resultsmentioning
confidence: 99%
“…In paired samples where pH was measured ( n = 27), pH was significantly different between first-draw and flushed samples ( p < 0.05). pH may influence the occurrence of L. pneumophila in distribution systems and building water, 108 though one laboratory study reported that L. pneumophila can grow in water with pH values ranging from 5.5 to 9.2. 103 A 2021 cooling tower study suggested that high pH (9.6) may be a technique for L. pneumophila control, though the authors noted this may be related to a reduction in protozoan hosts at high pH.…”
Section: Resultsmentioning
confidence: 99%